Emotional Dynamics in EFL Writing: The Interplay of Proficiency, Enjoyment, and Boredom - Hartono, Dang Arif; Prima, Stefanus Angga Badara (EJI (English Journal of Indragiri): Studies in Education, Literature, and Linguistics, 2025)
Foreign language writing can be a challenging and emotionally complex experience for learners. In fact, the literature has shown that learners’ emotions significantly influence foreign language acquisitionDespite the acknowledged influence of emotions in language learning, research specifically examining the interplay between proficiency, enjoyment, and boredom in EFL writing contexts, particularly among Indonesian university students, remains scarce. This correlational study investigated the interrelations between language proficiency, foreign language writing enjoyment (FLWE), and foreign language writing boredom (FLWB) among university students in Indonesia. The Oxford Quick Placement Test (QPT) was utilized to assess the participants’ proficiency level, while FLWE and FLWB scales were used to measure emotional dimensions. The findings revealed moderate positive correlations between proficiency and FLWE (r = .48, p < .01) and moderate negative correlations between proficiency and FLWB (r = -.58, p < .001). Additionally, a significant inverse relationship between FLWE and FLWB (r = -.53, p = .001) was identified. These findings suggest that higher proficiency fosters greater enjoyment and reduces boredom in writing activities. Implications for educators include scaffolding tasks to match proficiency levels and fostering positive learning environments to enhance engagement.